OXIDIZED TYPE OF COPPER ORES AT BOZYMCHAK SKARN DEPOSIT (KYRGYZSTAN) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
At the gold-copper skarn deposit Bozymchak, the main types of ores are skarn and serpentinite, the secondary type of ores is the oxidized type. The mineral composition and description of the oxidized type is given. Some results of technological studies of oxidized ores are given in comparison with sulfide ores.
Keywords: Tien-Shan; skarn; serpentinite; copper; concentrate; phase composition